New onset of loss of smell or taste in household contacts of home-isolated SARS-CoV-2-positive subjects - Boscolo-Rizzo, Paolo (Eur Arch Otorhinolaryngol, 2020)
PURPOSE: To estimate the prevalence of smell or taste impairment in household contacts of mildly symptomatic home-isolated SARS-CoV-2-positive patients. METHODS: Cross-sectional study based on ad hoc questions. RESULTS: Of 214 mildly symptomatic COVID-19 patients managed at home under self-isolation, 179 reported to have at least one household contact, with the total number of no study participants contacts being 296. Among 175 household contacts not tested for SARS-CoV-2 infection, 67 (38.3%) had SARS-CoV-2 compatible symptoms, 39 (22.3%) had loss of smell or taste with 7 (4.0%) having loss of smell or taste in the absence of other symptoms. The prevalence of smell or taste impairment was 1.5% in patients tested negative compared to 63.0% of those tested positive for SARS-CoV-2 (p < 0.001). CONCLUSION: Smell or taste impairment are quite common in not-tested household contacts of mildly symptomatic home-isolated SARS-CoV-2-positive patients. This should be taken into account when estimating the burden of loss of sense of smell and taste during COVID-19 pandemic, and further highlights the value of loss of sense of smell and taste as a marker of infection.